Calotes emma alticristatus (reptilia, squamata: agamidae) in Kelantan, peninsular Malaysia - Hashim, Rosli; Liat, L.B.; Sen, Y.H.; Sofian-Azirun, Mohd; Diah, S.Z.M.; Belabut, D. (2009)
In Peninsular Malaysia the agamid lizard Calotes emma Gray 1845 is known to be represented by the subspecies Calotes emma emma Gray 1845. Recently several specimens were encountered in Jeram Linang, Machang, Kelantan Darul Nairn. These belong to a different subspecies, Calotes emma alticristatus Schmidt 1925. This subspecies occurs in Thailand and South China. It constitutes a new record for the lizard fauna of Peninsular Malaysia.